A novel method to improve carboxymethyl cellulose performance in the flotation of talc. (15th January 2019) - Liu, Cheng; Zhang, Wencai; Song, Shaoxian; Li, Hongqiang
Graphical abstract: Magnesium ions dissolved from lizardite lattice at acid condition that adsorbed on the talc surface at pH 8.5 and enhanced the adsorption of CMC on talc surface. Highlights: A method to improve CMC depression on talc floatability was proposed. CMC completely depressed talc flotation when the pulp pH was adjusted from 4.0 to 8.5. Chalcopyrite was more efficiently separated from talc when using the proposed method. Mg 2+ dissolved from talc lattice at pH 4 then adsorbed onto talc surface at pH 8.5. Mg 2+ promoted CMC adsorption on talc surface and enhanced its depression performance. Abstract: A novel method to improve carboxymethyl cellulose (CMC) performance in talc flotation is described in this paper. Micro-flotation results showed that using CMC as the depressant, strong depression on talc floatability was observed when the pulp pH was adjusted from low (4.0) to high (8.5), which improved the separation performance between chalcopyrite and talc. Zeta potential measurements illustrated that talc surface charge was less negative when the pH was regulated from acid to base than the situation that the pulp pH was altered from base to acid. ICP test and XPS results indicated that more magnesium ions were dissolved from the talc lattices at pH 4 and the hydrolyzed species of magnesium cations were adsorbed onto the talc surfaces when the pulp pH was adjusted to 8.5, and thus promoting the CMC adsorption on the talc surfaces, which further decreased its floatability.